The role of the Military District Command (Kodim) 0732/Sleman in cultivating the state defense values towards adolescents during the Covid-19 pandemic - Samuel Asdianto Limbongan; Armaidy Armawi; Ahmad Zubaidi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2022)
Juvenile delinquency is a social issue in society. Adolescents are prone to commit activities that contradict Pancasila values. During the Covid-19 pandemic, the criminal cases in the Sleman regency have increased. In this situation, Kodim 0732/Sleman takes an important role in overcoming the criminal problems caused by the lack of state defense values understanding among adolescents. The current study aims to analyze the factors causing juvenile delinquency and the strategies to rehabilitate and educate adolescents about state defense values. It employed the descriptive qualitative research method. The main data of the research were derived from observation, interviews, and documentation. The data were analyzed through several processes namely data reduction, data display, and data verification. The results of this study found Kodim 0732/Sleman acts as a role model for the adolescents to cultivate the state defense values and depicts the facts of the regional defense condition during the Covid-19 pandemic. The conclusion of this study is The Kodim 0732/Sleman needs to establish a division or personnel who are directly responsible for the programs related to state defense values cultivation, especially for adolescents.